The Effect of Self Efficacy and Work Discipline on Employee Performance at Ciamis Regional General Hospital - Elsha Pamelianda Hermawan; Fetty Poerwita Sary (Eduvest - Journal of Universal Studies, 2025)
Hospitals are pillars of the health system, requiring healthcare workers who excel in technical skills and overall performance, supported by resources that yield superior health products and services. However, at Ciamis Regional Hospital, employee performance remains below the set targets and has declined annually. This decline is partly due to low self-confidence and suboptimal work discipline, as data from July to August 2024 revealed that over 50% of employees did not properly implement work discipline. Based on these observations, this research assesses self-efficacy, work discipline, and employee performance at Ciamis Regional General Hospital, and examines how self-efficacy and work discipline affect performance. The study employs a descriptive causal design with a quantitative approach. A total of 276 employees were selected using probability sampling. Data were collected via questionnaires and analyzed using Structural Equation Modeling (SEM) with Smart-PLS software. Results indicate that self-efficacy significantly and positively influences performance, and when combined with effective work discipline, performance improves further. Based on these findings, it is recommended that the hospital enhance self-efficacy and work discipline through mentoring, targeted training, performance awards, and rigorous adherence to work procedures supported by regular evaluation and feedback, ultimately aiming to improve service quality and overall employee performance.